Cross-Cultural Research in Cognitive Psycholinguistics: Analysis of Linguistic Diversity and Cognitive Processes - Yuliya Boyko; Oksana Sierhieieva; Olena Matsiuk; Denys Dmytroshkin; Nataliia Levytska (Forum for Linguistic Studies, 2024)
The study explores the integration of cognitive and psycholinguistic parameters in language education, focusing on designing communicative tasks to enhance oral proficiency in English among university students. Consciousness and meta-linguistic attention are highlighted as critical factors influencing communicative competence. A longitudinal observational study was conducted with second-year students at Khmelnytsky National University, focusing on the Department of Germanic Philology and Translation Studies. Both Bachelor’s and Master’s students participated in the study, which spanned an academic semester. The methodology involved systematic observation of English class interactions, where tasks integrating cognitive (fluency, accuracy, complexity) and psycholinguistic parameters simulated authentic communicative situations.The findings reveal that traditional approaches treating communication as merely a teaching tool are inadequate for developing language competence. Effective communication in English classes required tasks blending simulation and authenticity, significantly enhancing oral competence. A comprehensive approach incorporating cognitive and psycholinguistic considerations resulted in measurable improvements in students’ fluency, accuracy, and complexity in oral discourse. This study highlights the need for dynamic, engaging tasks that reflect the complexities of real-world communication, enriching students’ linguistic and cognitive abilities while fostering deeper engagement with the language. The results advocate for curriculum reforms and instructional designs prioritizing authentic communicative tasks, equipping students with skills to navigate diverse communicative situations. Such an approach can reshape university-level language teaching and better prepare students for global citizenship and intercultural communication, ultimately bridging the gap between classroom learning and real-world applications.